2023
DOI: 10.3390/nu15071725
|View full text |Cite
|
Sign up to set email alerts
|

Akkermansia muciniphila Cell-Free Supernatant Improves Glucose and Lipid Metabolisms in Caenorhabditis elegans

Abstract: To explore the mechanism by which Akkermansia muciniphila cell-free supernatant improves glucose and lipid metabolisms in Caenorhabditis elegans, the present study used different dilution concentrations of Akkermansia muciniphila cell-free supernatant as an intervention for with Caenorhabditis elegans under a high-glucose diet. The changes in lifespan, exercise ability, level of free radicals, and characteristic indexes of glucose and lipid metabolisms were studied. Furthermore, the expression of key genes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Lipids were lowered and immune function was modulated by four weeks of treatment with Akkermansia muciniphila 41 . Metabolism of glucose and lipids is improved by cell-free supernatants from Akkermansia muciniphila 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Lipids were lowered and immune function was modulated by four weeks of treatment with Akkermansia muciniphila 41 . Metabolism of glucose and lipids is improved by cell-free supernatants from Akkermansia muciniphila 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Khmaladze et al demonstrated that cell lysates of Lactobacillus reuteri DSM 17938 reduced UV-R-induced inflammatory cytokines IL-6 and IL-8 and protected the skin barrier [24]. Wu et al found that the cell-free supernatant of Akkermansia muciniphila, as a postbiotic, has the potential to prevent obesity and improve disorders of glucose metabolism [25].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increased autophagy of aging or senescent cells may have improved lifespan in L. fermentum postbiotic-fed C. elegans , as this has been studied as a mediator of lifespan extension in multiple studies and organisms [ 133 ]. Recently, cell-free supernatants of Akkermansia muciniphila extended lifespan while reducing ROS levels and oxidative damage [ 134 ]. A. muciniphila postbiotic also modulated metabolic functions, which was indicated by upregulation of glucose metabolism (i.e., gsy-1 , pygl-1 , and pyk-1 ) and lipid metabolism (i.e., acs-2 , cpt-4 , and tph-1 ) genes and, conversely, a downregulation of fat-7 , which regulates fatty acid biosynthesis [ 134 ].…”
Section: Geroprotective Effects Of Postbiotics In C Elegansmentioning
confidence: 99%
“…Recently, cell-free supernatants of Akkermansia muciniphila extended lifespan while reducing ROS levels and oxidative damage [ 134 ]. A. muciniphila postbiotic also modulated metabolic functions, which was indicated by upregulation of glucose metabolism (i.e., gsy-1 , pygl-1 , and pyk-1 ) and lipid metabolism (i.e., acs-2 , cpt-4 , and tph-1 ) genes and, conversely, a downregulation of fat-7 , which regulates fatty acid biosynthesis [ 134 ].…”
Section: Geroprotective Effects Of Postbiotics In C Elegansmentioning
confidence: 99%